Pengaruh Orientasi Pasar dan Orientasi Kewirausahaan terhadap Kinerja Penjualan UMKM pengrajin kulit (Studi pada Sentra Industri Pengrajin Kulit Desa Sukaregang, Garut) - Fajar Gilang Garnida; Wahyu Hidayat (Universitas Diponegoro, 2018)
Leather is a material commonly used and well-known by Indonesian people. Its used to make crafts in the form of jackets, purses, wallets, belts and hats. Leather has been famous in the world and becomes a trend of a good fashion among children, teenagers and parents. The leather craftsmen are facing strictly competition inside and outside the city so should be able to innovate continually. The aims of this research is to determine the effect of Market Orientation (X1) and Entrepreneurship Orientation (X2) and its effect on Sales Performance (Y) at SME (Small-Medium Enterprise) of Sukaregang Village, Garut. The type of this research is explanatory research with 25 respondents who have SME (Small-Medium Enterperise) of Sukaregang Village, Garut leather product that has been established for at least three years and have at least two functions employees. Questionnaires and interviews is used in collecting data and using Likert scale. In the data analysis using validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression analysis, multiple linear regression analysis and test of significance (t-test and F test) by SPSS 20.0. The results show that market orientation and entrepreneurship orientation has good categorization while the sales performance has a high categorization. There is influence of market orientation to sales performance with t value (4,229)> t table (1.713), influence of entrepreneurship orientation to sales performance with t value (3.059)> t table (1.713), and influence market orientation and entrepreneurship orientation on sales performance with the value of F value (10.124)> F table (3.44). Based on the results all independent variables in this study have an influence on the dependent variable either simultaneously or partially. Sukaregang Village Leather Craftmens, Garut should be able to innovate continually and know their customers so they can market the product in according with their respective markets.